Reward-related decision making and long-term weight loss maintenance - Brockmeyer, Timo; Simon, Joe J.; Friederich, Hans-Christoph (Physiology & behavior, 2017)
Background: Heightened sensitivity towards reward and insensitivity towards disadvantageous consequences may constitute a driving factor underlying unrestricted food intake and consequent weight gain in people with overweight and obesity. Therefore, the present study applied a behavioral economics approach to investigate the potential contribution of poor reward-related decision making to unsuccessful long-term weight loss maintenance (i.e. weight cycling). Based on previous research, it was expected that successful long-term weight loss maintainers would show a better performance in a gambling task than their less successful counterparts. Methods: Reward-related decision making was assessed post hoc using the Game of Dice Task in a total of 33 overweight and obese women who had either (a) successfully maintained initial weight loss of at least 10% of their body weight over one year or (b) had regained weight until at least their initial body weight prior to weight reduction (i.e. showed weight cycling). Results: The groups did not differ in terms of age, current body weight, magnitude of initial weight reduction, educational level, and global intelligence level. As hypothesized, however, the group of successful long-term weight loss maintainers performed significantly better (i.e. showed less impulsive, more advantageous choices) in the Game of Dice Task than their less successful counterparts. Conclusions: The findings suggest that poor reward-related decision making is associated with weight cycling which is considered a key concern in weight loss treatments for overweight and obesity. Furthermore, the findings speak in favor of specific psychological interventions that are designed to bolster reward-related decision making.